EFEKTIVITAS GLOBAL POSTURAL RE-EDUCATION EXERCISE DAN EDUKASI TERHADAP NYERI PUNGGUNG BAWAH NON-SPESIFIK PADA PEREMPUAN DI LTQ IQRO’ JATIMAKMUR - ACHIRDA, NUR; PAMBUDI, RESTU ARYA; MAULIDA, CHOLIFAH NUR (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Background: Non-specific lower back pain (NSLBP) represents a significant subset of musculoskeletal disorders. Epidemiological data suggest a predisposition towards females as a risk factor. Physiotherapy has an important role in non-specific LBP conditions. Objective: This study aims to evaluate the effectiveness of GPR exercises combined with educational interventions in managing non-specific lower back pain among women. Methods: Employing a quasi-experimental design, this study utilized a two- group pretest-posttest methodology. A total of 36 participants meeting the inclusion and exclusion criteria were allocated into two groups: Group I (n=18) received GPR exercises and educational interventions, while Group II (n=18) received only educational interventions. Pain intensity was quantified using the Visual Analog Scale (VAS). Interventions were administered bi-weekly over a six-week period. Results: Subsequent analysis using a paired sample t-test showed a significant reduction in pain in the intervention group (p < 0.05) and the education control group (p < 0.05. An independent t-test on the mean pain before and after intervention showed a significant difference (p < 0.05). Conclusion: There is a difference in the effectiveness of GPR exercise and education in reducing non-specific low back pain in women at LTQ Iqro'.